Psychological models in sport psychology: A preliminary investigation - Collins, D.; Winter, S. (European Journal of Sport Science, 2020)
Applied psychology is characterised by a variety of theoretical models, informing distinct approaches to classification, explanation, and intervention in service-delivery. Such theoretical or psychological models include behavioural, biological, cognitive, humanistic, psychodynamic, and social paradigms, with exposure to these models and attitude formation occurring within the structured university-based stage of sport psychology development. It is, therefore, important for the sport psychological domain to investigate developing attitudes, given these models inform subsequent professional practice and decision making. Accordingly, the present study explored the attitudes of Stage-1 sport psychology students through a modified form of the Maudsley Attitude Questionnaire (34 males, Mage = 24.71 years, SD = 7.23 and 42 females, Mage = 24.76 years, SD = 6.20). The questionnaire was designed to assess attitudes across eight psychological models (e.g. biological, cognitive) and four sport psychology issues (pre-performance anxiety, a lack of confidence, depression, and eating disorders). Analyses of variance demonstrated significant main, model, and interaction effects. No one psychological model was endorsed by all respondents, with model endorsement varying significantly as a function of the issue presented. Principal Axis Factoring revealed a large contribution attributable to cognitive-behavioural and `eclectic` (mixed elements of social constructionism, biological, and psychodynamic) models. In contrast, the spiritual model represented low levels of participant endorsement and application. Investigation of Stage-1 students can promote an evidence-based understanding on currently developing attitudes and inform the development of sport psychology education, supervision of training routes, and subsequent professional delivery.